Effect of Ag-doping on morphology, structure, band gap and photocatalytic activity of bio-mediated TiO2 nanoparticles - Tasnuva Zahan Liza; Md Mahamud Hasan Tusher; Foysal Anwar; Maria Ferdous Monika; Kazi Faiza Amin; F.N.U. Asrafuzzaman (Results in Materials, 2024)
The production of nanoparticles using biogenic synthesis techniques is becoming more prominent due to its diverse applications. In this research, the extract from mango leaf was utilized to fabricate a green method for producing Ag-doped and undoped TiO2 nanoparticles that is non-toxic, economical, and environmentally favorable. Titanium isopropoxide (TTIP) was used as a precursor for Ag-doped and undoped TiO2 nanoparticle production, where the concentrations of the dopant material silver were 2.5 and 3%. Acquired undoped and Ag-doped TiO2 nanoparticles were characterized using several analytical techniques. The morphological, structural, and photocatalytic activity were evaluated using XRD, SEM, EDX, and UV–Vis spectroscopy. In the XRD analysis, undoped and Ag-doped TiO2 nanoparticles indicated the formation of an anatase phase, but there was no rutile phase. The photocatalytic activity and nanoparticles’ band gap were assessed using UV–Vis spectroscopy. The UV–Vis Spectroscopy also revealed a reduced band gap energy (Eg) of Ag-doped TiO2 nanoparticles than the undoped TiO2 Nanoparticles (NPs). The development of photocatalytic activity and features of the “Red-shift” characteristic was established by the progressive photo-degradation of Methylene Blue (MB). The SEM analysis revealed that Ag-doped TiO2 nanoparticles showed more agglomeration than the undoped sample. The average particle size of undoped TiO2 nanoparticles was 38.33 nm, and the size gradually increased for 2.5% and 3% Ag-doping. Utilizing EDX analysis, the doping of Ag+ in the TiO2 lattice structure was confirmed. We can predict from the findings that utilizing biosynthesized TiO2 nanoparticles can be an excellent option for water purification, dye-sensitized solar cells, photo-degradation process, etc., in the long run.